Design and Development Trends in Modern Drilling Tools: A Review - Lewandowska, Aleksandra; Salamon, Szymon; Leksycki, Michał; Feldshtein, Eugene (Zielona Góra: Uniwersytet Zielonogórski)
Drilling is one of the most common machining operations, and its capabilities are utilized on lathes, drilling machines, conventional milling machines, as well as various CNC machines. This paper provides an overview of modern drill bit designs and current trends in their development. The study considers twist drills, three-flute drills, drills with index able inserts, step drills, solid carbide drills, and other types of drills widely used in industry.
Keywords: drilling tools; drill bit design; drill geometry; cemented carbide drills; indexable insert drills